2020
DOI: 10.1029/2019sw002391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reference Heights of O/N2 and ∑O/N2 Based on GUVI Dayside Limb Measurement

Abstract: We define a new thermospheric concept, the reference heights of O/N 2 , referring to a series of thermospheric heights corresponding to the fixed ratios of O to N 2 number density. Here, based on Global Ultraviolet Imager (GUVI) limb measurement, we compare O/N 2 column density ratio (∑O/N 2 ) and the reference heights of O/N 2 . We choose the transition height of O and N 2 (transition height hereafter), a special reference height at which O number density is equal to N 2 number density, to verify the connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Yue et al (2019) showed that GUVI data has an SAO in both [O] and O/N 2 with equinoctial peaks, which are in phase between the lower (8.4 × 10 −4 Pa) and upper thermosphere (6.35 × 10 −6 Pa). Similar results were also obtained by Yu et al (2020). We estimate 8.4 × 10 −4 Pa to be ∼140-160 km.…”
Section: Discussionsupporting
confidence: 91%
“…Yue et al (2019) showed that GUVI data has an SAO in both [O] and O/N 2 with equinoctial peaks, which are in phase between the lower (8.4 × 10 −4 Pa) and upper thermosphere (6.35 × 10 −6 Pa). Similar results were also obtained by Yu et al (2020). We estimate 8.4 × 10 −4 Pa to be ∼140-160 km.…”
Section: Discussionsupporting
confidence: 91%
“…∑O/N 2 is obtained by integrating densities of O and N 2 from infinity down to an altitude where the column number density of N 2 is 1 × 10 17 /cm 2 and thus it is actually defined on a constant pressure surface with no altitude information (Correira et al., 2020). O and N 2 number densities decrease exponentially with altitude, so the column number densities of O and N 2 at the altitude where the N 2 column number density is 1 × 10 17 /cm 2 is mainly from altitudes immediately above this level (∼140–180 km) (Yu, Ren, Le, et al., 2020; Yu, Ren, Yu, et al., 2020). This altitude region encompasses most of LBH radiance and minimizing the uncertainty in ∑O/N 2 as a function of 135.6 nm/LBH.…”
Section: Introductionmentioning
confidence: 99%
“…In situ measurements provide thermospheric information either at a fixed altitude, or mix altitude variations with other spatial and temporal changes. Disk‐viewing measurements provide the ratio between column O and column N 2 density (∑O/N 2 ), that is, the ratio of the integrated O and N 2 densities from infinity down to an altitude where the N 2 column density is 10 17 cm −2 (~140 km, e.g., Kil et al., 2011; Meier et al., 2005; Stephan et al., 2008; Yuan et al., 2015; Yu, Ren, Yu, et al., 2020; Zhang et al., 2004). This implies that ∑O/N 2 is a quantity defined in pressure coordinates.…”
Section: Introductionmentioning
confidence: 99%